Structural Studies on Metal Complexes of 2-Furoin Oxime - Mehta, B.H.; Nagarkoti, B.S. (Asian Journal of Chemistry, 2010)
Transition metal complexes of 2-furoin oxime have been synthesized and characterized by elemental analysis, molar conductance, magnetic and spectral data. Various bonding features were established on the basis of IR spectral data. The electronic spectral data are calculated. The structural geometry is assigned on the basic of various spectral findings.